A new look at transformation of relation as an Usuli theory - Belal` Shaker; Professor, Department of Islamic Jurisprudence and Fundamentals, Faculty of Theology and Islamic Studies, Ferdowsi University, Mashhad, Iran.; Mohammadhasan Haeri (مطالعات تطبیقی فقه و اصول مذاهب)
Transformation of relation as a discussed problem under the title of contradiction of arguments in usul al-fiqh, is a way to apply the rules of contradiction of arguments, when there are more than two contrary arguments. According to this way, all relations and connections between arguments are seen and based on specific criteria, rules of contradictions are applied. This article, through description and analyzing of usuli written texts tries to answer if transformation of relation can be recognized as a scientific theory and presented to academic forums. The hypothesis is that this way of solving contradiction can be introduced as the theory of transformation of relation to ‘ilm al-usul. To reach to the mentioned goal and to prove the theory of the article (being an usuli theory), the proposed definitions for a scientific theory, focusing on fiqhi and usuli theories, were analyzed; accepted characteristics of scientific theories were derived and analyzed; and lastly, the essential qualities of transformation of relation were applied on the definitions. The conclusion was that the transformation of relation could be presented as a scientific theory in usul al-fiqh to academic forums. So to explain it there need to see it as a theory with its all details and aspects not just a viewpoint.